Teologi Pendidikan Kristen dalam Keluarga Berdasarkan Ulangan 6:4-9 dan Implementasinya pada Model Pembelajaran Berbasis Teori Pemrosesan Informasi - Mikha Agus Widiyanto; Daniel Ronda (UKI Press, 2022)
In the implementation of Family Christian Education, an appropriate learning model is needed, so that teaching can be stored well in the child's memory. Deuteronomy 6:4-9 is not only a theological concept in Family Education but also a learning model that is relevant to information processing theory. This study aims to determine the implementation of the learning model based on Deuteronomy 6:4-9 which is based on information processing theory. This study uses a qualitative approach using exegesis methods and literature review. The results of the study show that the content of teaching in family education based on Deuteronomy 6:4-9 introduces children to the One God from an early age, which must be taught repeatedly and binds to the child, so that teaching will be stored in long-term memory. Teaching that is done by parents repeatedly shows that the content of the teaching has important values and benefits that will bring attention to the child, which is then encoded. Applying the learning model by teaching repeatedly will make children's understanding and knowledge sharpened, stored and can be retrieved in solving problems and forming person with a strong faith.